Longitudinal changes in electromyographic activity of masseter and anterior temporalis muscles before and after alloplastic total joint replacement in patients with temporomandibular ankylosis: a prospective study. Issue 7 (September 2022) - Singh, Apoorva; Roychoudhury, Ajoy; Bhutia, Ongkila; Yadav, Rahul; Bhatia, Renu; Yadav, Poonam
Abstract: The purpose of the study was to evaluate the longitudinal changes in electromyographic (EMG) activity of the masseter and temporalis muscles before and after temporomandibular joint (TMJ) total joint replacement (TJR) in ankylosis patients. A prospective longitudinal study was designed on patients undergoing unilateral or bilateral TMJ-TJR. EMG activity at rest and maximal voluntary contraction (MVC) was recorded for the muscles preoperatively (T0), and at one-week (T1) and six-month (T2) follow up. The study sample was composed of 10 (male: female 2.3:1) patients undergoing TMJ-TJR. The number of unilateral and bilateral cases was three and seven, respectively. In both unilateral and bilateral cases a statistically significant reduction in EMG activity of the masseter and anterior temporalis muscles was observed at T1. At T2, EMG activity of the muscles was found to be approaching the preoperative value. In unilateral cases, when the affected side at T0, T1, and T2 was compared with T0 for the unaffected side, statistically significant differences were seen for the masseter. In the case of the temporalis, similar results were seen except at T2 for the postural rest position. The results indicate that re-attachment of the masseter and temporalis muscles occurs progressively post TMJ-TJR.